Dialogic virtuosity of messages on Instagram account @Sevinch.cos.id as an effort to get consumer engagement - Soekamto, Abdurazan Aprilinggar; Abdullah, Nisa Nurmauliddiana (Bricolage : Jurnal Magister Ilmu Komunikasi, 2025)
This research examines the strategies employed by the Instagram account @Sevinch.cos.id, a local natural ingredient-based skincare brand, to increase consumer engagement through social media. Using a descriptive qualitative approach and case study method, this research analyzes how Sevinch builds relationships with audiences through the dialogic virtuosity of the message, which includes the approach in delivering the message, the consistency and relevance of the message, the use of cultural elements, and direct interaction with customers. The data collection process was conducted through observation, interviews, and literature studies, which were then analyzed using triangulation to ensure the accuracy and validity of the research results. The results showed that Sevinch implemented four main strategies. First, they deliver messages in a simple, relaxed, informative, and interactive way, so that they are easily accepted by the audience. Second, Sevinch adapts the message to the needs of consumers while maintaining the consistency of its brand identity, such as highlighting natural ingredients in every promotion. Third, the cultural element of using natural ingredients is put forward as the main attraction to support the trend of environmentally friendly skincare that is increasingly in demand. Fourth, utilizing social media features such as comments, direct messages (DM), polls, and question and answer sessions to build more personal and emotional communication with consumers. These strategies have proven effective in building trust, loyalty, and consumer engagement, in accordance with the Coordinated Management of Meaning (CMM) theory that emphasizes the importance of understanding messages contextually, as well as compliance gaining theory that focuses on persuasive communication to influence audience behavior. This research provides important insights for businesses on how to utilize social media as a strategic communication tool to build long-term relationships with consumers. By emphasizing consistency, relevance, and active interaction, brands can create stronger engagement, increase trust, and strengthen consumer loyalty to the products or services offered.